(untitled) (GEOmedia, 2009)
SAT-Expo Europe 2009 and integrated applications SAT-Expo was an exhibition held in Rome from the 19th until the 21st of March. SAT-Expo is the main euro-mediterranean satellite technology and services showcase. The 2009 edition featured 114 companies, 20 meeting sessions and more than 5400 attendees. This year’s edition brought 10 foreign delegations, including France and China, together. The event focused on all the major topics regarding the satellite sector, including navigation, Earth Observation and communications.